2021
DOI: 10.3390/jpm11121381
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota Composition across Normal Range Prostate-Specific Antigen Levels

Abstract: Animal studies have shown the interaction between androgens and the gut microbiome directly and indirectly; however, limited evidence from human studies is available. To evaluate the association between prostate-specific antigen (PSA) levels within the normal range, reflective of androgen receptor activity, and the gut microbiota composition, a cross-sectional analysis was performed in 759 Korean men aged between 25 and 78 years with normal PSA levels of ≤4.0 ng/mL. We evaluated the biodiversity of gut microbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Escherichia Shigella, XIII AD3011 group, and Acidaminococcaceae, Clostridiales were predicted to an increased risk of getting BPH, while Flavonifractor, Marvinbryantia, Ruminococcaceae UCG009, Eisenbergiella, Methanobacteriaceae, Selenomonadales, Methanobacteriales, Negativicutes, and Methanobacteria were on the contrary. Both the direct and indirect impacts of the gut microbiome on the androgens have been demonstrated in animal studies, which contribute to benign prostatic hyperplasia and Escherichia Shigella was found to be correlated with raised testosterone 59 , 60 . Consistent with our study, Clostridiales can convert primary bile acids into toxic secondary bile acids and convert glucocorticoids into androgens by side-chain cleavage, which is likely to contribute to progression of benign prostate hyperplasia 61 .…”
Section: Discussionmentioning
confidence: 96%
“…Escherichia Shigella, XIII AD3011 group, and Acidaminococcaceae, Clostridiales were predicted to an increased risk of getting BPH, while Flavonifractor, Marvinbryantia, Ruminococcaceae UCG009, Eisenbergiella, Methanobacteriaceae, Selenomonadales, Methanobacteriales, Negativicutes, and Methanobacteria were on the contrary. Both the direct and indirect impacts of the gut microbiome on the androgens have been demonstrated in animal studies, which contribute to benign prostatic hyperplasia and Escherichia Shigella was found to be correlated with raised testosterone 59 , 60 . Consistent with our study, Clostridiales can convert primary bile acids into toxic secondary bile acids and convert glucocorticoids into androgens by side-chain cleavage, which is likely to contribute to progression of benign prostate hyperplasia 61 .…”
Section: Discussionmentioning
confidence: 96%
“…Numerous studies have demonstrated that prostatic in ammation signi cantly contributes to elevated serum levels of PSA [18 , 19]. Recently, a study reported associations between microbial diversity, taxonomy signatures in the gut microbiome of men, and serum PSA levels [20].…”
Section: Introductionmentioning
confidence: 99%